Project BEAR ISLAND: DEPAS ocean-bottom seismometer operations in the Fram Strait in 2007-2008 ... - Schweitzer, Johannes; Schmidt-Aursch, Mechita; Krüger, Frank; Guterch, Aleksander (PANGAEA, 2024)
BEAR ISLAND (The Dynamic Continental Margin Between the Mid-Atlantic-Ridge System (Mohns Ridge, Knipovich Ridge) and the Bear Island Region) is an interdisciplinary project exploring the stress conditions and sources, and the dynamics and deformation characteristics of the continental margin between the Mid-Atlantic Ridge and Bear Island from its top sedimentary cover to its imprint in the upper mantle. In this region the margin includes an extremely thick sedimentary wedge and steep slopes, with at least one major paleo-fracture zone cutting through the wedge. Recent studies in this area indicate very low seismic velocities in the lithosphere and the stress field undergoes an extensional-compressional transition. It is therefore of particular interest to understand the structural architecture, the stress and the dynamics of the whole region because of its natural hazard exposure and the processes involved in the formation of the margin and the opening of the North Atlantic.To achieve this, deep seismic ...